Role of MSTd Extraretinal Signals in Smooth Pursuit Adaptation - Ono, Seiji (Oxford University Press, 2012)
The smooth pursuit (SP) system is able to adapt to challenges associated with development or system drift to maintain pursuit accuracy. Short-term adaptation of SP can be produced experimentally using a step-ramp tracking paradigm with 2 steps of velocity (double-step paradigm). Previous studies have demonstrated that the macaque cerebellum plays an essential role in SP adaptation. However, it remains uncertain whether neuronal activity in afferent structures to the cerebellum shows changes associated with SP adaptation. Therefore, we focused on the dorsal–medial part of medial superior temporal cortex (MSTd), which is part of the cortico-ponto-cerebellar pathway thought to provide extraretinal signals needed for maintaining SP. We found that 54% of the SP-related neurons showed significant changes in the first 100 ms of response correlated with adaptive changes of initial pursuit. Our results indicate that some cortical neurons in MSTd could be inside the circuit involved in SP adaptation. Furthermore, our sample of MSTd neurons started their discharge on average 103 ms after SP onset. Therefore, we suggest that extraretinal signals carried in MSTd might be due to efference copy of pursuit eye velocity signals, which reflect plastic changes in the downstream motor output pathways (e.g., the cerebellum).